EVALUASI NILAI LITERASI DAN NUMERASI RAPOR PENDIDIKAN SMP NEGERI 3 SATU ATAP LUBUK BESAR TAHUN 2024-2025 - Lilis Karlina; Marlina Ummas Genisa; Sri Wardhani; Meli Astriani (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
This study aims to evaluate the literacy and numeracy scores of students at SMP Negeri 3 Satu Atap Lubuk Besar through an analysis of their report cards in 2024 and 2025. This research was conducted using a qualitative-descriptive method by reviewing educational report cards. The results of the study show that literacy scores increased from 76.74% in 2024 to 91.11% in 2025, while numeracy scores increased from 58.14% to 86.84%. The increase in the education report card scores is related to improvement efforts involving the entire school community. Several improvement measures that were taken included teacher training, the implementation of deep learning, and the strengthening of literacy and numeracy activities. Several challenges that still need to be addressed include the implementation of innovative literacy and numeracy activities, the lack of interest in reading among students, and the low level of prior knowledge among students. Recommendations from this study include improving the quality of learning, particularly in literacy and numeracy activities at school. The results of this evaluation are expected to help improve the quality of learning in order to improve students' literacy and numeracy skills.